Ragam Kosakata dalam E-Book Kemendikbud sebagai Wujud Pendidikan Multikultural di SD/MI - Nurdianah, Lutfiyan; Ixfina, Ficky Dewi (Universitas Indraprasta PGRI Jakarta, 2024)
Kemendikbud has been compiling e-books of folktales from various regions since 2016, which are used as media to enhance students' literacy skills of early childhood into high school levels. The aim of compiling these books is to introduce the diverse ethnicities, cultures, and languages of Indonesia to the younger generation. This cultural introduction in the education sphere is commonly referred to as multicultural education. This research employs a descriptive quantitative approach with discourse analysis of literacy using several e-books of folktales published by Kemendikbud. The study presents findings and observations regarding the variety of vocabulary and readability in these books. The analysis results indicate that, in terms of readability, some of the folktales published by Kemendikbud are suitable for the intended readership, while others are less suitable. This is evidenced by the Fry readability graphs of two different books. Meanwhile, concerning vocabulary diversity, there are elements of local culture and language incorporated, indicating that these folktale books support the implementation of multicultural education. The e-books as media and learning resources for students represent a manifestation of multicultural education. They serve as a means to introduce and celebrate the rich cultural diversity of Indonesia, fostering an inclusive learning environment that respects and values different ethnicities, cultures, and languages.